Extension of UNIFAC to associating systems - Foco, Gloria (2001)
An extended UNIFAC group contribution model for the prediction of activity coefficients in associating mixtures was presented recently (Mengarelli et al.,1999). In the present work the model is applied to solutions containing alcohols, water, carboxylic acids and inert components. The residual UNIFAC local composition term is re-parameterized in order to take into account only dispersive forces between associating and inert functional groups. Good representation of vapor-liquid and liquid-liquid equilibrium, as well as infinite dilution activity coefficients is achieved by using a single set of group interaction parameters.